Analisis Pengaruh Etnisitas dalam Pengisian Jabatan Struktural di Pemerintah Kabupaten Muaro Jambi: Pasca Pilkada 2017 - Wahid, Makmun; Haryadi, Haryadi (Jurnal Analisis Sosial Politik, 2018)
The playing of Javanese ethnic politics in the struggle for political office and bureaucracy in Muaro Jambi District gave rise to negative interactions for Javanese ethnicity and other ethnicities in Muaro Jambi Regency. What is done by Javanese is their attempt to show their dominance over other ethnic groups in Muaro Jambi Regency .Where previously the concept of the son of the region became a discourse for the process of filling these positions. This study uses qualitative research methods, with a case study approach and triangulation data analysis techniques. From the method used a description of how the rise of Javanese ethnic politics provided a way for them to dominate political office and especially for bureaucratic office. In addition, the pattern of support will be fragmented for the same identity, especially related to ethnic similarities. Theneutrality of the bureaucrats in the elections shows that politicalparties in Indonesia do not institutionalize well.Not surprisingly, after the election is over, it has an indirect impact on the mechanism of rotation, mutation and promotion of structural positions in the Muaro Jambi District government. Where the placement of people carried out in the body of the bureaucracy will be dominated by Javanese ethnic influences, which then slowly 'get rid of' other ethnicities. Clearly, such a mechanism tends to prioritize the patron client approach rather than prioritizing the performance of individual officials.This paper suggests the need for interventions both regulative and technical so that the mechanism for filling public positions in the post-election bureaucracy in Indonesia in the future can produce government elites that are more qualified and with integrity. The use of new digital mediais an offer for renewing the paradigm of the Post-Election Bureaucracy. Bermainnya politik etnis Jawa dalam perebutan jabatan politik dan birokrasi di Kabupaten Muaro Jambi melahirkan interaksi negatif bagi etnis Jawa dan etnis-etnis lain di Kabupaten Muaro Jambi. Apa yang dilakukan oleh etnis Jawa merupakan upaya mereka untuk menunjukkan dominasinya terhadap etnis lain di Kabupaten Muaro Jambi. Dimana sebelumnya konsep putra daerah menjadi wacana bagi proses pengisian jabatan-jabatan tersebut. Penelitian ini menggunakan metode penelitian kualitatif, dengan pendekatan studi kasus dan teknik analisis data triangulasi. Dari metode yang digunakan tersebut diperoleh gambaran bagaimana kebangkitan politik etnis Jawa memberikan jalan bagi mereka untuk mendominasi jabatan politik dan jabatan birokrasi. Selain itu, pola dukungan pun akan terfragmentasi atas kesamaan identitas semata, terutama terkait kesamaan etnis. Tidak netralnya para birokrat dalam Pilkada menunjukkan bahwa partai politik di Indonesia tidak melembaga dengan baik. Tidak heran, jika setelah Pilkada usai, hal itu memberikan dampak secara tidak langsung pada mekanisme rotasi, mutasi dan promosi jabatan-jabatan struktural di lingkup pemerintahan Kabupaten Muaro Jambi. Dimana penempatan orang yang dilakukan di dalam tubuh birokrasi akan didominasi oleh pengaruh etnis Jawa, yang kemudian pelan- pelan ‘menyingkirkan’ etnis lainnya. Jelasnya, mekanisme seperti itu cenderung lebih mengedepankan pendekatan patron klien ketimbang mengutamakan kinerja dari individu pejabat. Tulisan ini mengisyaratkan perlunya intervensi secara regulatif maupun tekhnis agar mekanisme pengisian jabatan publik di dalam birokrasi pasca Pilkada di Indonesia ke depan dapat menghasilkan elit-elit pemerintahan yang lebih berkualitas dan berintegritas. Penggunaan media digital baru menjadi tawaran bagi pembaharuan paradigma Birokrasi Pasca Pilkada.